An Economic Approach to Article 82 - Report by the European Advisory Group on Competition Policy - Jordi Gual; Martin Hellwig; Anne Perrot; Michele Polo; Patrick Rey; Klaus M. Schmidt; Rune Stenbacka (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This report argues in favour of an economics-based approach to Article 82, in a way similar to the reform of Article 81 and merger control. In particular, we support an effects-based rather than a form-based approach to competition policy. Such an approach focuses on the presence of anti-competitive effects that harm consumers, and is based on the examination of each specific case, based on sound economics and grounded on facts.
urn:nbn:de:bvb:19-epub-13469-7
Keywords: D4; 330; Competition Policy; Abuse of Market Power; Article 82